2012
DOI: 10.1172/jci60224
|View full text |Cite
|
Sign up to set email alerts
|

MCM4 mutation causes adrenal failure, short stature, and natural killer cell deficiency in humans

Abstract: An interesting variant of familial glucocorticoid deficiency (FGD), an autosomal recessive form of adrenal failure, exists in a genetically isolated Irish population. In addition to hypocortisolemia, affected children show signs of growth failure, increased chromosomal breakage, and NK cell deficiency. Targeted exome sequencing in 8 patients identified a variant (c.71-1insG) in minichromosome maintenance-deficient 4 (MCM4) that was predicted to result in a severely truncated protein (p.Pro24ArgfsX4). Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
209
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(219 citation statements)
references
References 26 publications
8
209
0
2
Order By: Relevance
“…29 In humans, a recessive condition called Meier-Gorlin syndrome, which is caused by an N-terminal truncation of MCM4 leads to increased chromosomal fragility in patients' lymphocytes and dermal fibroblasts. 30,31 A similar phenotype of DNA breaks and gaps was also observed in human aneuploid cell lines. Indeed, we demonstrated that the low levels of MCM2-7 are responsible for the replication defects in aneuploids, as restoring near wild-type levels of MCM2-7 partially alleviated the phenotype.…”
Section: Mechanisms Leading To Genomic Instabilitysupporting
confidence: 58%
“…29 In humans, a recessive condition called Meier-Gorlin syndrome, which is caused by an N-terminal truncation of MCM4 leads to increased chromosomal fragility in patients' lymphocytes and dermal fibroblasts. 30,31 A similar phenotype of DNA breaks and gaps was also observed in human aneuploid cell lines. Indeed, we demonstrated that the low levels of MCM2-7 are responsible for the replication defects in aneuploids, as restoring near wild-type levels of MCM2-7 partially alleviated the phenotype.…”
Section: Mechanisms Leading To Genomic Instabilitysupporting
confidence: 58%
“…A human MCM4 mutation (destabilizing the MCM2-7 complex) was recently reported concurrently by two groups who studied consanguineous families, and the resulting phenotype was found to be associated with immune deficiency (NK cells), adrenal insufficiency and short stature [79,80]. Patient fibroblasts showed chromosome fragility [79].…”
Section: Mcms and Genomic Stabilitymentioning
confidence: 97%
“…Patient fibroblasts showed chromosome fragility [79]. The susceptibility of these patients to cancer is not currently known [80]. An MCM8 disruption and alternative splice form have been noted in hepatic carcinoma [11] and choriocarcinoma [12], respectively.…”
Section: Mcms and Genomic Stabilitymentioning
confidence: 99%
“…Recently, mutations in nicotinamide nucleotide transhydrogenase (NNT) a mitochondrial membrane constituent which is involved in detoxification of reactive oxygen species were also associated with FGD . Notably, mutations in minichromosome maintenance-deficient 4 (MCM4) which forms part of a protein complex which is essential for DNA replication and genome stability are associated with a variant of FGD found in the Irish Traveller population where adrenal failure is accompanied by short stature, chromosome instability, and natural killer cell dysfunction (O'Riordan et al, 2008;Gineau et al, 2012;Hughes et al, 2012).…”
Section: Mc2rmentioning
confidence: 99%